Rebel yell ; In the crossfire ; Coup lites [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
The seventh coup attempt and the most serious threat to the Philippine government. An analysis of why it happens. Looks at the media coverage its responsibilities and limitations. Also talks to psychologists to find out why the crowd seems to be an integral part of every Philippine coup. Looks at what people have been moved to do is a eresult of this serious threat to the country.
Rebel yell (19 min.) -- In the crossfire (16 min.) -- Coup lites (15 min.)
VHS.
Keywords: Coups d'etat -- Philippines; Mass media -- Influence; Philippines -- History -- Coups d'etat, 1989.